(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
We have studied the structural and magnetic properties of Zn1-xFexTe thin films grown under Te-rich flux condition with almost same Fe composition, x = 1.3%, on both undoped and nitrogen (N) acceptor doped ZnTe buffer layer by molecular beam epitaxy (MBE). Structural analysis by XRD and XAFS reveals that Zn0.987Fe0.013Te films are mainly composed of pure diluted phase with substitutional Fe atoms on the Zn-site in the zinc-blende (ZB) ZnTe in both cases. However, the magnetization measurement using SQUID shows distinctly different magnetic properties among these films; a linear dependence of magnetization on magnetic field (M-H), typical of van-Vleck paramagnetic behavior of Zn0.987Fe0.013Te film grown over undoped ZnTe turns into ordinary paramagnetic behavior with S-shape M-H curve for film grown on N-doped ZnTe buffer layer, [N] ≈ 1020 cm-3 which may reflect the impact of interfacial holes provided by N-acceptors on the valence state of substitutional Fe. J. Bangladesh Acad. Sci. 48(1); 27-34: June 2024